Coastal EFL Students’ Critical Reading Skills in Detecting Online Deception: A Descriptive Study - Gatot Subroto; Arsyistawa Haqqi; Encik Abdulhajar; Candradewi Wahyu Anggraeni (Lembaga Bale Literasi, 2026)
In the digital era, critically evaluating online information is paramount for coastal EFL university students. While current research predominantly focuses on self-perceived competence, a significant gap remains regarding students’ actual performance in detecting digital deception. This study investigates the alignment between students’ self-perceived abilities and their actual proficiency in evaluating online threats. Employing a quantitative descriptive design, 32 undergraduate students from one of state universities in Sumatra were selected via purposive sampling. Data were collected using a self-report questionnaire and a performance-based test featuring authentic scenarios, specifically fraudulent e-commerce promotion and .apk-based courier scams. Findings revealed a significant discrepancy: while self-perceived confidence remained moderate (M=3.22), their actual performance in detecting deception was remarkably high (92.7%). Qualitative data, analyzed through thematic coding, indicates that senior students employed sophisticated technical reasoning, whereas juniors relied on intuition. These results suggest that coastal EFL students possess strong “survival literacy” yet lack academic confidence, highlighting a need for pedagogical bridges between practical safety and critical analysis.